2012
DOI: 10.1155/2012/716392
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Cavitating Flow through Waterjet Propulsors

Abstract: A computational-fluid-dynamics-based modeling effort to capture flow through an axial flow waterjet propulsor is presented. The effort covered the waterjet flow over a wide range of flow coefficients and into cavitation-driven breakdown. The computations are presented in cavitation at two values of flow coefficient through a series of decreasing operating inlet total pressure. The computational results are compared to experimental measurements. Suction-surface and tip-gap cavitation patterns are presented and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…As N * keeps decreasing and the values of T and H * start dropping steeply, the numerical model deviates significantly from the test data. A similar trend can be observed in the CFD results reported in the study of Lindau et al [32]. The reasons for this behaviour were first adduced by Chesnakas et al [51] and later confirmed by Tan et al [12] and Chen et al [13].…”
Section: Thrust Breakdown Numerical Assessmentsupporting
confidence: 84%
See 3 more Smart Citations
“…As N * keeps decreasing and the values of T and H * start dropping steeply, the numerical model deviates significantly from the test data. A similar trend can be observed in the CFD results reported in the study of Lindau et al [32]. The reasons for this behaviour were first adduced by Chesnakas et al [51] and later confirmed by Tan et al [12] and Chen et al [13].…”
Section: Thrust Breakdown Numerical Assessmentsupporting
confidence: 84%
“…In particular, Zhao et al [41] and Guo et al [42] formulated modified versions of the ZGB cavitation model to account for the effect of vorticity on cavitation. In this path, Lindau et al [32] obtained good results for the same axial-flow waterjet pump described in the present paper, employing a steady-state RANS approach with homogeneous multiphase assumption and a mass-transfer rate cavitation model. The adopted cavitation model is characterized by empirical coefficients set to default values to provide good results for general applications, e.g., simple geometries like hydrofoils or complex machines.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…There is a large body of literature on the effect of cavitation on the performance of axial turbomachines, including tests of waterjet pumps performed in the present facility [48,49]. They show that for cavitation to adversely affect the overall machine performance, almost the entire suction side of the rotor blades has to be covered by attached cavitation [50]. For a less developed extent of cavitation, such as the present conditions, it has a negligible effect on the overall machine performance.…”
Section: Resultsmentioning
confidence: 94%